KORELASI AKTIVITAS BELAJAR DENGAN HASIL BELAJAR KELAS IV SEKOLAH DASAR NEGERI 17 PONTIANAK KOTA - Intan Intan; Budiman Tampubolon; Tahmid Sabri (Universitas Tanjungpura, 2022)
AbstractThis study aims to describe the correlation between students' learning activities during home study during the covid-19 pandemic and the learning outcomes of students of grade IV of State Elementary School 17 Pontianak Kota. The method used is a descriptive method with a form of interrelationship studies using correlation studies. This study is a population study with a total of 32 students. The data collection techniques in this study are indirect communication techniques and documentary study techniques. The data collection tools used are questionnaires and documents of average values. The results showed that students' learning activities during home study during the covid-19 class IV of State Elementary School 17 Pontianak Kota amounted to 76.5% in the category of